2015
DOI: 10.2147/copd.s88326
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cognitive impairment in long-term oxygen therapy-dependent COPD patients

Abstract: BackgroundA number of studies have shown that COPD, particularly in its later and more severe stages, is associated with various cognitive deficits. Thus, the primary goal of the present study was to elucidate the extent of cognitive impairment in patients with long-term oxygen therapy-dependent (LTOTD) COPD. In addition, this study aimed to determine the effectiveness of two cognitive screening tests, the Mini-Mental State Examination (MMSE) and the Montreal Cognitive Assessment (MoCA), for COPD patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…It is a recognized fact that long-term oxygen therapy (LTOT) is able to protect signiicantly (p < 0.022) the cognitive functions from COPD-induced deterioration. Another fact is that the patients with mild cognitive impairment COPD induced are unaware of the risk that involves repetitive desaturations to produce conversion from mild cognitive impairment to dementia, if nothing is done with LTOT [38,39].…”
Section: Copd: Fundamental Pathophysiological Mechanisms Susceptible mentioning
confidence: 99%
See 1 more Smart Citation
“…It is a recognized fact that long-term oxygen therapy (LTOT) is able to protect signiicantly (p < 0.022) the cognitive functions from COPD-induced deterioration. Another fact is that the patients with mild cognitive impairment COPD induced are unaware of the risk that involves repetitive desaturations to produce conversion from mild cognitive impairment to dementia, if nothing is done with LTOT [38,39].…”
Section: Copd: Fundamental Pathophysiological Mechanisms Susceptible mentioning
confidence: 99%
“…(2) It is now recognized that not only continuous, but also intermitent hypoxia (eforts, daily activities and sleep) can by repetition cause changes in brain neurochemistry and structure [7,36]. Regular use of supplemental oxygen therapy has been shown to decrease the risk for cognitive impairment in patients with COPD [37,38,95].…”
Section: Therapeutic Implications; Preventive Strategiesmentioning
confidence: 99%
“…In a similar study www.journals.viamedica.pl conducted by Nasilowski et al [12], it has been reported that FEV 1 and PaCO 2 values of patients who used OC on average for at least 15 hours daily, are better than the relevant parameters of individuals using OC less frequently. In the study conducted by Karamanlı et al [21], it has been also reported that cognitive status of COPD patients who use regularly OC is better than in those using the device irregularly [21]. At the end of our study, it was determined that if daily OC usage time is increased, clinic parameters of patients may improve.…”
Section: Discussionmentioning
confidence: 53%
“…Many studies have shown that patients with COPD usually have cognitive impairment either globally or in certain cognitive domains. It has been reported that 42.0% of patients with COPD had moderate to severe cognitive impairment, whereas 14.0% of control subjects had cognitive dysfunction 54 . Concerning hypoxemia, the rate of neuropsychological deficit was 27.0% for mild hypoxemia but 62.0% for severe hypoxemia.…”
Section: Prevalence and Impact Of Cognitive Impairment In Copdmentioning
confidence: 99%
“…62 This suggests that cognitive function may be reversibly-impaired during exacerbation. 63 However, cognitive impairment in the patients during exacerbation has been associated with poor compliance with medication and oxygen therapy. This poor compliance increases the risk of repeated acute exacerbation.…”
Section: Prevalence and Impact Of Cognitive Impairment In Copdmentioning
confidence: 99%